Detección molecular de Ascochyta rabiei en garbanzo (Cicer arietinum L.) - Pastor, Silvina Estela; Paccioretti, Mauro Andres; Torres, Laura; Otero, Maria Laura; Rossi, Marcelo; Taborda, Ricardo; Conci, Luis Rogelio (Asociación Argentina de Fitopatólogos (AAF), 2025)
Poster y resumen